ANALISIS PENERAPAN PROBLEM BASED LEARNING PADA PEMBELAJARAN BAHASA INDONESIA MEMADUKAN PEMBELAJARAN INTERAKTIF JELAJAH LINGKUNGAN - Nadhifah, Siti Hajarun Nadhifah; Nursiwi Nugraheni (Jurnal Tunas Pendidikan, 2025)
The aim of this research is to analyze the effectiveness of implementing the Problem Based Learning (PBL) model in Indonesian language learning, especially in vocabulary material, by combining interactive learning through exploring the school environment. This research aims to improve students' understanding of vocabulary, develop critical thinking skills, and create a fun and contextual learning experience. With direct interaction in the surrounding environment, it is hoped that students can more easily relate new vocabulary in a fun way. The application of this learning was carried out at SDN Ngesrep 03 Semarang using observation, test and data collection techniques. Data analysis techniques are carried out by reducing data, presenting data, and conclusions. The results of the research showed that 10% of students got scores in the range 90-100, 37% of students got scores in the range 80-89, then students who got scores in the range 70-79 and 60-69 had the same percentage of scores, namely- 26% each. students had an average of 74, median 65, mode 80, highest score 90 and lowest score 60. There were 5 students who did not meet the KKM. Keyword: Learning Outcomes, PBL, Vocabulary